The Landscape of MSME Research in Developing Countries Based on Bibliometric Analysis and Visualization of Global Collaboration Networks - Loso Judijanto; Zainal Arifin (Westscience Press, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in supporting economic growth, employment creation, and poverty reduction in developing countries. Despite their importance, the rapidly growing body of literature on MSMEs has produced a fragmented research landscape that requires systematic mapping to understand its development and emerging directions. This study aims to analyze the landscape of MSME research in developing countries using a bibliometric approach. Data were collected from the Scopus database and analyzed using bibliometric techniques and visualization tools, particularly VOSviewer, to identify publication trends, collaboration networks, and dominant research themes. The results reveal that MSME research has developed into a multidisciplinary field connecting themes such as entrepreneurship, innovation, financial inclusion, sustainability, and digital transformation. Collaboration network analysis shows that several authors and institutions act as key connectors in the research network, while countries such as India and Indonesia emerge as major contributors to global MSME research. Keyword co-occurrence and overlay analyses indicate that earlier studies primarily focused on entrepreneurship and innovation, whereas more recent research emphasizes digital transformation, technology adoption, and sustainable development goals. These findings demonstrate that MSME research is evolving toward addressing contemporary challenges related to digitalization and sustainable economic development. This study provides a comprehensive overview of the intellectual structure and development trends of MSME research and offers insights for future research directions in the field.